2020
DOI: 10.1186/s12876-020-01506-6
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distance from navel as a risk factor for bowel obstruction associated with feeding jejunostomy after esophagectomy: a retrospective cohort study

Abstract: Background Placement of feeding jejunostomy (PFJ) during esophagectomy is an effective method to maintain adequate nutrition, but is associated with serious complications such as bowel obstruction and jejunal torsion. The purpose of the current study was to analyze the incidence, clinical features, and risk factors of bowel obstruction associated with feeding jejunostomy (BOFJ) after PFJ. Methods This was a retrospective cohort study of 70 patients who underwent esophagectomy with three-field lymph node diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…BOFJ is caused by the small intestine torsion of the anal side over the jejunostomy into the gap between the abdominal wall fixation sites. Kamada et al 14 reported that the vertical distance between the jejunostomy and navel was associated with BOFJ. We also reported that the proximity of the jejunostomy to the midline of the abdomen is a risk factor for BOFJ 8 and that the risk of torsion due to internal herniation into the gap and strangulation may increase depending on the position of the jejunostomy site.…”
Section: Discussionmentioning
confidence: 99%
“…BOFJ is caused by the small intestine torsion of the anal side over the jejunostomy into the gap between the abdominal wall fixation sites. Kamada et al 14 reported that the vertical distance between the jejunostomy and navel was associated with BOFJ. We also reported that the proximity of the jejunostomy to the midline of the abdomen is a risk factor for BOFJ 8 and that the risk of torsion due to internal herniation into the gap and strangulation may increase depending on the position of the jejunostomy site.…”
Section: Discussionmentioning
confidence: 99%
“…BOFJ is caused by torsion of the anal side of the small intestine into the gap between the catheter insertion site and the abdominal wall xation site. Kamada et al [14] reported that the vertical distance between the jejunostomy and navel was associated with BOFJ.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ‘free distal flow’ has been reported as an important factor in spontaneous closure [ 11 ]. Button jejunostomy has an acute bending angle between the jejunostomy and abdominal wall compared with Wizel jejunostomy [ 6 ], which may interfere with the natural flow of intestinal fluid to the distal intestinal tract and lead to REF.…”
Section: Discussionmentioning
confidence: 99%
“…Button jejunostomy was performed in the same method in all patients during oesophagectomy. The details of button jejunostomy creation were described in a previous report [ 6 ]. We inserted a 24-Fr button-type catheter (IDEAL BUTTON®; Olympus Medical Systems Co.Ltd, Tokyo, Japan) to the jejunum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation